Studi Etnometodologi Berfokus pada Proses Internalisasi “Panca Jiwa Pondok” di Lingkungan Pesantren - Hanifah Noviandari (Elsalima (Salam Institute), 2024)
This study aims to explore a deep understanding of the internalization of the five principles of pesantren among all stakeholders, especially the students. Another objective is to explore the essence and implementation of Panca Jiwa Pondok from Pesantren which has been initiated by the founders of Pondok Modern Darussalam Gontor Putri Campus 3 in Ngawi, East Java, and non-alumni of Gontor Islamic boarding schools adopt this. This research uses qualitative methods with an ethnomethodological approach. This method focuses on the resources, procedures, and practices that groups or community members use to generate and recognize perceived social realities. This research was conducted at Pondok Modern Darussalam Gontor Putri Campus 3, Ngawi. Data was collected through natural interviews in everyday life involving researchers in the pesantren environment. The data analysis process is carried out descriptively since the first data collection, so as not to wait for excessive data accumulation. This research reveals three main characteristics of Panca Jiwa Pondok: strengthening social piety, strengthening intrapersonal aspects, and spirituality. The process of internalizing